Further analysis of psychotropic medication and severe problem behavior. (15th August 2021) - Falligant, John M.; Bednar, Molly K.
Abstract: Cox et al. (2021) recently outlined a number of analytic methods (i.e., procedures for estimating effect size, conditional rates, and nonparametric partial correlation tests) that may help quantify the relative contributions of psychotropic medication and behavioral interventions on problem behavior among individuals with intellectual and developmental disorders. The purpose of the current study was to examine the generality of these methods by applying these procedures in a novel clinical context (i.e., a hospital‐based inpatient unit for severe problem behavior). We extended the procedures described by Cox to include a larger sample size, cases with more frequent, severe and treatment‐resistant problem behavior, cases with both medication decreases and increases, and cases with at least one similar class of psychotropic medication in common (i.e., atypical antipsychotics). This work remains a proof of concept, but we replicated a number of the preliminary findings from Cox et al. Implications for future research and medication monitoring practices are discussed.